Navigating access and benefit sharing in international trade of endemic species: The case of Colombia's poison frogs (Dendrobatidae) - German Forero‐Medina; Luz Dary Acevedo; Andrés Balcazar; Marcela Delgado; Alfred DeGemmis; Susan Lieberman; Felber Arroyave (Conservation Science and Practice)
Abstract Wildlife is an important global commodity that generates significant revenue along the supply chain, including economic benefits in range states for sought‐after species. However, international trade in wild species is often associated with over‐exploitation and illegal extraction. To regulate, monitor, and ensure the sustainability of such trade, over 180 countries have ratified the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES). Using national data collected through CITES processes, we undertook a network analysis to evaluate the structure and dynamics of international trade in six CITES‐listed species of Colombian endemic poison frogs (Dendrobatidae). We assessed the magnitude of the international trade and the countries that were reporting legal imports/exports, both before and after Colombia allowed legal exports of these species, to examine the changes associated with Colombia's export legalization and to draw conclusions about the country's role and benefits from trade in these species. Our analyses show that, for over two decades, international trade of CITES‐listed species likely in contravention of the Convention resulted in significant exports—and likely greater financial benefits—accruing in non‐range states through reported captive breeding programs. Although the market was reconfigured when Colombia legalized the export of certain endemic frog species, non‐range states with founder stocks obtained from unknown and possibly illegal sources continue to account for a significant portion of the trade volume of some species (mostly, Phyllobates spp.). We discuss the importance of enforcing regulations and collaborations that promote better traceability of international commerce of endemic species to ensure the legitimacy of transactions, economic benefits for origin countries, and the conservation of species in the wild.